Pengaruh Store Atmosphere, Lokasi Dan Kualitas Pelayanan Terhadap Minat Beli Ulang Pelanggan Kopi Nako Summarecon Bekasi - Anike Suci Badriawan; Febriyanti Nona (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This research is motivated by developments in the digital era today the business world is growing so rapidly and business ventures that are in great demand by customers, such as one example is a cafe or coffee shop. If the better the marketing strategy on the business venture, the faster the business venture develops. This study aims to determine the effect of store atmosphere, location and quality of service to the customer's interest in re-buying coffee Nako Summarecon Bekasi. This study uses descriptive research methods with a quantitative approach. The population of this study is Coffee customers Nako Summarecon Bekasi. The number of samples was 170 respondents, while the data collection technique used was non-probability sampling, namely purposive sampling technique. This research data in the form of primary data sourced from questionnaires that have been tested for validity and reliability, while data analysis using descriptive analysis and multiple regression analysis. The results of the t-test in this study showed thatthe store atmosphere, location and quality of Service have a significant effect on re- purchase interest so that the hypothesis in this study can beaccepted. The results of the f test showed that the store atmosphere, location and quality of service simultaneously significantly affect the re- purchase interest.